-84=-7(2m+6)+8m

Simple and best practice solution for -84=-7(2m+6)+8m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -84=-7(2m+6)+8m equation:


Simplifying
-84 = -7(2m + 6) + 8m

Reorder the terms:
-84 = -7(6 + 2m) + 8m
-84 = (6 * -7 + 2m * -7) + 8m
-84 = (-42 + -14m) + 8m

Combine like terms: -14m + 8m = -6m
-84 = -42 + -6m

Solving
-84 = -42 + -6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '6m' to each side of the equation.
-84 + 6m = -42 + -6m + 6m

Combine like terms: -6m + 6m = 0
-84 + 6m = -42 + 0
-84 + 6m = -42

Add '84' to each side of the equation.
-84 + 84 + 6m = -42 + 84

Combine like terms: -84 + 84 = 0
0 + 6m = -42 + 84
6m = -42 + 84

Combine like terms: -42 + 84 = 42
6m = 42

Divide each side by '6'.
m = 7

Simplifying
m = 7

See similar equations:

| 1.5x+(18-1.5x)=18 | | X^3-125/5x-5 | | (5x+14y)+(3x+3y)= | | 700=464+7x | | -51+3= | | 7u-9=3u+5 | | X^3-135/5x-5) | | 3t-8=-11 | | x/3-6=10 | | y-18+y+x=180 | | 7x-5=-2x+4 | | -2y+14=3x | | 6h+5(3)=45 | | 5x+3(x-4)+12=2(4x+3) | | 2x+14=3x-31 | | 9r-9=-342 | | 4/3x-10=24 | | 7k-8(10)=45 | | -4=-9+v | | 4b-7=101 | | 45(n+6)=35n | | 2.56=x/2 | | -7=w+8 | | 2p+7=-53 | | (Y/6)4 | | 4x+1x+25+3x-5=2y-12 | | 8(9)+7a=79 | | 4c+6=-130 | | 5x-26=3x+20 | | 3+2(x+2)=9+3x | | (Y/-15)5 | | -8(x-2)=24 |

Equations solver categories